New Macroeconomic Evidence on Internal Migration in Sweden, 1967–2003. Issue 1 (2nd January 2016) - Gärtner, Svenja
Abstract : Gärtner S. New macroeconomic evidence on internal migration in Sweden, 1967–2003. Regional Studies . This paper gives new empirical evidence on internal migration's macroeconomic impact factors in Sweden from 1967 to 2003. Variables from the labour market, demography and geography serve as explanatory factors. The dynamic panel model's estimation contradicts recent results arguing that wage differences play no role in migration in Sweden. The paper's results suggest that wages and unemployment rates work as push and pull factors. These results are constant over time, not a development following the solidarity wage policy's break-up. While younger people are more likely to move, the increasing female labour force participation has hampered migration, especially in recent years.